Development of Electronic-Public Relations Through "Mp Mobile Apps" for Optimization of Information Systems - Mohammad Syahidul Haq; Aditya Chandra Setiawan; Ima Widyanah; Najlatun Naqiyah; Firman Ashadi (Jurnal Penelitian Pendidikan IPA, 2023)
Good education management can certainly be carried out as effectively and efficiently as possible, which in the end is a positive response from users of educational services in the form of user satisfaction. There are several aspects to increase user satisfaction, one of which is information that is quickly received by the public and internal citizens of educational institutions. The method in this study uses the Waterfall Model from Winston Walker Royce, which has 5 stages (Analysis, Design, Implementation, Testing, and Maintenance). The purpose of this research is to emphasize the improvement of information services for department members and the general public, namely the quality of information services in a practical and integrated manner. The results of the â€œMP Mobile Appsâ€ development show that the "MP Mobile Apps" application has met the eligibility standards to be implemented with an average of each. The category is as much as 85%.